Studies on the yeast-hypha mediated virulence in Candida species - Paudyal, Anuja (Kansas State University, 2022)
Candida albicans is a commensal and opportunistic fungal pathogen in humans. The transition of oval yeast form to filamentous hypha form is one among the several virulence factors in C. albicans causing its pathogenesis. Compounds known to inhibit this transition and hyphal growth have potential as antifungal agents and prevent tissue invasion of fungus, if they do not harm the host. Gymnemic acid (GAs) is a small molecule known to inhibit hyphal formation in vitro and in an invertebrate animal model under hypha inducing environment. However, the mechanism of GAs mediated hypha inhibition in poorly known. Here, I present the work from four different but related studies on the morphology and pathogenesis of Candida species. The first two chapters describe studies aimed at understanding how C. albicans hyphal growth is inhibited by GAs at the molecular level. The chapters after that focus mainly on skin colonizing fungus Candida auris, its ability to form biofilms, identification of quorum sensing molecules, and the interaction of fungus with a skin resident bacterial pathogen, Staphylococcus aureus. The basic knowledge gained from the first two chapters helped us to decipher the pathogenesis mechanism of a newly emerged Candida species described in the latter chapters. Our first study has highlighted GAs as a potential antifungal compound. We evaluated the efficacy of GAs in a mouse model of systemic candidiasis and demonstrated that GAs treatment rescued mice from C. albicans-mediated death while mice without treatment did not survive. The survival of infected mice in the presence of GAs corresponded with the strongly reduced fungal burden in the kidney tissues and is possibly due to GAs-mediated block of hyphal cells preventing the spread of fungus. In our second study, we investigated the mode of action of GAs at molecular level. It is known that Nrg1 and Ume6 are negative and positive regulators of hyphal growth, respectively. Also, past and current studies from our laboratory showed GAs affect these genes. Therefore, we decided to identify proteins that associate with these regulators in the presence and absence of GAs. This will allow us to identify how GAs impact these regulatory pathways. For this we used a two-step tandem affinity purification approach followed by mass spectrometry. Addition of GAs to cells co-purified significantly more proteins as compared to controls without GAs. When these proteins were categorized using GO term analysis, majority of proteins were the proteins having DNA and RNA binding activity, proteins involved in hyphal growth and signaling, or ribosomal proteins. Our proteomics data suggested that GAs exposure to C. albicans recruit regulatory proteins at the transcriptional machinery that are known to promote budding and or suppress hyphal growth. The Ume6 copurified protein group have a relatively higher number of proteins having ligase activity involving synthesis of tRNA and amino acids when compared to Nrg1. We hypothesize there could be some cross talk between these regulatory proteins and the Hog1 pathway. In the third study, we investigated the Nrg1p in a recently emerged Candida species, C. auris, where the role of Nrg1p is unknown. C. auris primarily grows as yeast form. Based on immunofluorescence and proteomic methods, we found Nrg1p localized, surprisingly, on the cell surface of C. auris and was not directly involved in hyphal growth. Finally, the fourth study focused on C. auris’ interaction with one of the skin colonizing bacterial pathogens. C. auris shares its habitat with several microbes, including S. aureus. Both C. auris and S. aureus being skin dwellers, salt tolerant, and drug-resistant, they were found to survive together in in vitro growth conditions that mimic the skin surface. They formed dual-species biofilms that had increased virulence (e.g. hemolytic activity of S. aureus). We surmised their synergistic biofilm growth and augmented bacterial virulence may involve inter-kingdom quorum signaling. While much is known about quorum sensing (QS) signaling in S. aureus, nothing is known about it in C. auris. Extraction and analyses of QS molecules from C. auris growth medium revealed presence of novel QS molecules. To our knowledge, this is the first study to show that C. auris produces quorum sensing molecules different from farnesol secreted by C. albicans which inhibits filamentation in C. albicans. Together, results from our studies added new insights into GAs-mediated hyphal inhibition in C. albicans, and GAs may be developed as novel antifungal agents to prevent hyphae-related fungal infections. Further, the synergistic interaction of C. auris and S. aureus in skin mimicking conditions with increased virulence highlight the potential risk to human health. Understanding their virulence mechanism better may help us to manage these pathogens effectively.
Keywords: Candida albicans; Candida auris; Antifungal compound; Morphogenesis; Candida-bacteria interaction; Quorum sensing